Stepwise protein targeting into plastoglobules are facilitated by three hydrophobic regions of rice phytoene synthase 2 - Yu, Ji Su; You, Min Kyoung; Lee, Yeo Jin; Ha, Sun-Hwa (Frontiers in Plant Science, 2023)
Plastoglobules (PGs) are plastidial lipid droplets enclosed by a polar monolayer born from the thylakoid membrane when plants require active lipid metabolism, including carotenogenesis, under the environmental stress and during plastid transition. Despite the fact that many proteins are reported to target PGs, their translocation mechanism has remained largely unexplored. To elucidate this process, we studied the influence of three hydrophobic regions (HR)—HR1 (1–45th aa), HR2 (46–80th aa), and HR3 (229–247th aa)—of rice phytoene synthase 2 (OsPSY2, 398 aa), which has previously shown to target PGs. As results, HR1 includes the crucial sequence (31–45th aa) for chloroplast import and the stromal cleavage occurs at a specific alanine site (64th aa) within HR2, verifying that a N-terminal 64-aa-region works as the transit peptide (Tp). HR2 has a weak PG-targeting signal by showing synchronous and asynchronous localization patterns in both PGs and stroma of chloroplasts. HR3 exhibited a strong PG-targeting role with the required positional specificity to prevent potential issues such as non-accumulation, aggregation, and folding errors in proteins. Herein, we characterized a Tp and two transmembrane domains in three HRs of OsPSY2 and propose a spontaneous pathway for its PG-translocation with a shape embedded in the PG-monolayer. Given this subplastidial localization, we suggest six sophisticated tactics for plant biotechnology applications, including metabolic engineering and molecular farming.